Removal of Cr(vi) from aqueous solution using magnetic modified biochar derived from raw corncob. (14th November 2019) - Hoang, Le Phuong; Van, Huu Tap; Nguyen, Lan Huong; Mac, Duy-Hung; Vu, Thuy Trang; Ha, L. T.; Nguyen, X. C.
Abstract : Magnetic modified-corncob biochar with an impregnation ratio of iron at 20% (w/w) was used for removal of Cr(vi ) from aqueous solution. Abstract : Magnetic modified-corncob biochar with an impregnation ratio of iron at 20% (w/w) was used for removal of Cr(vi ) from aqueous solution. Batch adsorption experiments were conducted to investigate the adsorption isotherm, kinetics and mechanism of Cr(vi ) onto MCB20. The results indicated that the maximum adsorption capacity achieved was 25.94 mg g −1 . The adsorption kinetic data were found to fit best to the pseudo-second order model with a high correlation coefficient ( R 2 = 0.992). The adsorption mechanisms of Cr(vi ) onto MCB20 were electrostatic attraction, anion exchange and adsorption coupled-reduction. The adsorption mechanisms occurring between Cr(vi ) anions and MCB20 were due to mainly the contribution of Fe3 O4 present in the corncob biochar structure after magnetization by FeCl3 . Among the aforementioned mechanisms, adsorption coupled-reduction plays a vital role in removal of Cr(vi ) by enhancement of the reduction of Cr(vi ) to Cr(iii ) through generation of electron-donor groups (hydroxyl groups) on the MCB20 surface. Then, Cr(vi ) interacted with the electron-donor groups and Cr(vi ) is reduced to Cr(iii ). Besides, Fe 2+ ions in the MCB20 structure were simultaneously oxidized to Fe 3+ ions and enhanced the transformation of Cr(vi ) into Cr(iii ). The reduced Cr(iii ) cations, finally, were adsorbed by MCB20 through substitution of Fe 3+ with Cr 3+ under acidic conditions, complexation with surface functional groups of MCB20 and formation of Cr(OH)3 . This study both developed a new way to produce a low cost adsorbent for removal of Cr(vi ) from aqueous solution and solved waste by waste.